Clinical effectiveness of esophageal stricture dilation using an improved endoscopic attachment cap in adults with eosinophilic esophagitis - Schoepfer, Alain M.; Biedermann, Luc; Kreienbuehl, Andrea; Safroneeva, Ekaterina; Saner, Catherine; Schreiner, Philipp; Greuter, Thomas; Straumann, Alex; Wakim El-Khoury, Jeanine (Endoscopy, 2025)
The improved endoscopic attachment cap has the following new features: 1) more rounded tip; 2) stepwise dilation in two 1-mm increments; 3) softer plastic, ensuring better contact with the endoscope tip; and 4) improved adhesive tape. We evaluated the feasibility and effectiveness of one-time esophageal stricture dilation using the new device in adults with eosinophilic esophagitis (EoE).Patients prospectively included in the Swiss EoE cohort with esophageal strictures (diameter ≤16 mm) and stricture-related symptoms underwent dilation with the new device. Symptoms were assessed using the Eosinophilic Esophagitis Activity Index patient-reported outcomes instrument before and 2 weeks after a single dilation.60 patients (median age 42 years; 75% male) were evaluated. Bougienage was successful in all patients. Median esophageal diameter increased from 12 mm (interquartile range [IQR] 11–14) to 16 mm (IQR 14–16; P < 0.001). Median symptom severity dropped from 36 points (IQR 22–62) to 0 (IQR 0–12; P < 0.001). No device became detached and no severe adverse events were reported. Post-dilation pain was recorded in 31.7% (19/60).Esophageal stricture dilation in adults with EoE using the improved endoscopic attachment cap was feasible, clinically effective, and environmentally friendly.